STRATEGIC MANAGEMENT OF SCHOOL PRINCIPALS IN IMPLEMENTING INNOVATIVE CURRICULUM BASED ON DEEP LEARNING TO STRENGTHEN 21ST CENTURY SKILLS - Asmar Baco; Masrur Yahya; Haeruddin; Moh. Bahzar; Akhmad Akhmad; Khusnul Khotimah (RADJA PUBLIKA, 2026)
This study aims to describe the principal's strategic management in implementing an innovative deep learning-based curriculum to strengthen 21st-century skills at SMP Negeri 1 Biatan, Berau Regency, East Kalimantan. A qualitative case study approach was employed. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed through data condensation, display, and conclusion drawing. Trustworthiness was ensured through source and method triangulation. Findings show the principal applies strategic management regularly and integratively. Strategic planning focuses on student-centered learning and 4C skills through school needs analysis and stakeholder collaboration. Strategic organizing is carried out through clear role distribution, curriculum team formation, regular coordination, teacher learning communities (Kombel SNESA), and flexible scheduling. Strategic implementation is realized through active discussion- and project-based learning, supported by academic supervision and continuous teacher development. Strategic supervision and evaluation are conducted through periodic instrument-based supervision with follow-up improvements and transparent communication to parents.